Update and reasoning out the best antihypertensive treatment - Bryce-Moncloa, Alfonso (2010)
Evolution in treatment of arterial hypertension has changed from monotherapy with high doses of diuretics as recommended by the "Joint National Committee I" (JNC) in 1977 to low doses of combined therapy as suggested by the JNC VII in 2003. A review of progress in antihypertensive therapies and current recommendations is done.